Effectiveness of Education Management of Private School Principals under Jurisdiction of Khon Kaen Educational Office - Agsonsua , Pha; Kositpimanvach, Ekarach (Dhammathas Academic Journal, 2020)
The objectives of this research were: 1) to study the effectiveness of education management of private schools under jurisdiction of Khon Kaen Educational Office, 2) to study the components of effectiveness of education management of private schools under jurisdiction of Khon Kaen Educational Office. There were 2 phases in conducting this research. Phase 1: rationate and related theories and the research literatures were studied to study the present condition by qualitative data collection of 127 principals and 3,000 teachers from 127 private schools with total population of 3,127. The sample groups were 97 private school principals and 341 teachers by simple random sampling. The instrument used in this research was a 5-level rating scale questionnaire with IOC of 0.84, and α-coefficient of 0.98. Data analysis was processed by computer program through frequency, means and standard deviation, and PNI Modified. Phase 2: qualitative data collection through focus group discussion which was done by purposive sampling of selected experts. The tools used in this process were tape recording and notetaking. Content analysis of the conceptual framework and other issues found, and finally concluded and summarized. The findings of this research were as follows: The effectiveness of education management of private schools ender jurisdiction of Khon Kaen Educational Office, in all, were at Moderate level. The research literatures were studied priorities from the highest to the lowest were, 1) learning achievement, 2) students’ character, 3) climate and environment, 4) satisfaction of all personnel concerned, 5) school change and development and 6) adaptability to continual change.